Laparoscopic resection of a paraganglioma behind the retrohepatic segment of the inferior vena cava: a case report and literature review - Wang, Wenda; Deng, Jianhua; Li, Hanzhong; Ji, Zhigang; Wen, Jin (Frontiers in Endocrinology, 2023)
Background: Due to the location of paragangliomas (PGLs) behind the retrohepatic segment of inferior vena cava (IVC), it is difficult to expose and resect the tumor. Case presentation: A tumor measuring 50×45×62cm behind the retrohepatic portion of IVC was found in a 51-year-old female with hypertention and diabetes mellitus. Although the test for catecholamine revealed no signs of disease, the enhanced CT scan, somatostatin receptor imaging and 131I-MIBG imaging revealed that the tumor was PGL. A three-dimensional printing was performed to visualize the tumor. The laparoscpic surgery for the PGL behind the retrohepatic segment of IVC was performed and the tumor was resected completely without causing any tissues injury. The pathologic diagnosis was PGL and the patient was able to recover well. Conclusions: This case demonstrates that laparoscopic surgery may be helpful in tumor accessibility, and could be used in the appropriate cases to remove PGLs that are located behind the retrohepatic segment of the IVC.